An observational, real‐life safety study of a 5‐grass pollen sublingual tablet in children and adolescents. Issue 8 (29th December 2014) - Eberle, Peter; Brueck, Helmut; Gall, Ralph; Hadler, Meike; Sieber, Jochen; Karagiannis, Efstrathios
Abstract Background The safety and efficacy of pre‐ and coseasonal sublingual allergen immunotherapy (SLIT) with a 5‐grass pollen sublingual tablet have been demonstrated in a randomized clinical trial (RCT) in children and adolescents. Observational, 'real‐life' studies can usefully complement the results of RCTs. Methods A prospective, open‐label, observational, multicentre post‐marketing study of children and adolescents (aged 5–17, with grass pollen‐induced allergic rhinitis) treated with the 5‐grass pollen sublingual tablet was performed between June 2009 and January 2011 in Germany. Adverse events (AEs) were recorded during consultations with the investigating physicians; AEs judged to have at least a possible causal link to the tablet were classified as adverse drug reactions (ADRs). Results Eight hundred and forty‐nine patients were enrolled (by 207 investigating physicians), 829 (mean ± s.d. age: 10.9 ± 3.3 yr) completed the study without major protocol deviations, and 796 were fully documented with respect to AEs. Ninety‐four of the 796 patients (11.8%) experienced at least one ADR on the first day of SLIT and 218 (27.4%) experienced at least one ADR during the study. Four hundred and sixty‐six of the 596 ADRs (78.2%) were mild or moderate. The most common ADRs were throat irritation (19.1% of the reactions), oral paresthesia (8.2%), oral pruritus (6.5%) and oedema mouth (6.2%). Serious ADRs occurred in five patients. No epinephrine use was reported. Seventy‐six of the 829 patients (9.2%) discontinued SLIT due to AEs. Tolerability was judged to be good or very good by patients (84.7%), parents (87.0%) and investigators (89.7%). Conclusions In clinical practice, pre‐ and coseasonal treatment with a 5‐grass pollen sublingual tablet is safe and well tolerated in children and adolescents.